The impact of microglial activation on blood-brain barrier in brain diseases - da Fonseca, Anna Carolina Carvalho; Matias, Diana; Garcia, Celina; Amaral, Rackele; Geraldo, Luiz Henrique; Freitas, Catarina; Lima, Flavia Regina Souza (Frontiers in Cellular Neuroscience, 2014)
The blood-brain barrier (BBB), constituted by an extensive network of endothelial cells together with neurons and glial cells, including microglia, forms the neurovascular unit. The crosstalk between these cells guarantees a proper environment for brain function. In this context, changes in the endothelium-microglia interactions are associated with a variety of inflammation-related diseases in brain, where BBB permeability is compromised. Increasing evidences indicate that activated microglia modulate expression of tight junctions, which are essential for BBB integrity and function. On the other hand, the endothelium can regulate the state of microglial activation. Here, we review recent advances that provide insights into interactions between the microglia and the vascular system in brain diseases such as infectious/inflammatory diseases, epilepsy, ischemic stroke and neurodegenerative disorders.